Domain decomposition with discrete element simulations using shared-memory parallel computing for railways applications - Hoang, T.M.P.; Saussine, G.; Dureisseix, D.; Alart, P. (European Journal of Computational Mechanics, 2012)
Numerical simulation with discrete elements leads to several issues for large-scale problems and long loading times, as for the granular dynamic simulations of the ballasted railway behaviour. To reduce computational costs, we study the use of two strategies: domain decomposition methods and shared-memory parallelisation with OpenMP. An example of a maintenance process, the tamping, on a portion of railway track with seven sleepers, is simulated.